The synthesis of novel crown ethers. Part IV. Coumarin derivatives of [18]crown-6 and cation binding from fluorescence spectra - (:unkn) unknown (Editura Stiintifica F. M. R., 1998)
4-H, 4-methyl and 4-phenyl-1-benzopyran-2-one derivatives of [18]crown-6 derivatives were synthesised from 6,7- and 7,8-dihydroxy-1-benzopyran-2-one reacting with pentaethylene glycol ditosylate in K2CO3/DMF/water. The products were identified by elemental analysis, EI-GC-mass spectra and IH-NMR spectroscopy. The Na+ association constants of some coumarin derivatives were determined with an ion selective electrode in water. The Na+ , K+, Ba2+ and Sr2+ binding role of such compounds were particularly observed as remarkable alterations in acetonitrile. The 1:1 associations constants of K+ and Na+ with some coumarin-[18]crown-6 derivatives estimated by this way in acetonitrile exhibited the utility of complexing enhanced quenching fluorescence spectra for the ion binding power of the such macrocycles.
Keywords: Cation binding; Coumarins; Fluorescence spectroscopy; Macrocyclic ethers